STUDI PEMANFAATAN LIMBAH BIOMASSA PERTANIAN SEBAGAI BIOADSORBEN UNTUK MENYERAP ION Cr - Arif Setiawan, Andi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
This study aims to assess the ability of agricultural biomass waste as material adsorbentÂ in the form of : rice husk, sawdust and peanut skins in total Cr ions adsorb. Ion concentration of 300 ppm Cr is used as much as 100 ml, with a contact time of 30, 60, 90, 120 and 150 minutes. The results showed the presence of intereaksi between bioadsorben with real-time contact with the Cr ions absorb 11.235 F count> F table 2.27 5%. Rice husk has the largest absorption than powders and porters gergai peanuts, respectively absorbance at 150 minutes contact time is 4.00 mg / g, 6.534 mg / g and 5.452 mg / g.Â Key words : ion Cr,Â waste agricultur biomass, rice husk, sawdust, peanut shell